Jamarun and Intan Mara: A Reflection of the Surau and Lapau People in the Community of Sumpur Kudus Sijunjung District (1950-2022) - Sukmawati, Peggy Indah; Nopriyasman, Nopriyasman; Zulqaiyyim, Zulqaiyyim (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research is directed at the struggle of two heads of families, with different Minangkabau socio-cultural backgrounds, how the socio-cultural environment affects their characters in educating their children. The method used in this study is a historical method through four stages, namely first, heuristic, which is the stage of data collection in the form of documents or books, articles, journals, and interviews. Second, source criticism is testing data by conducting internal and external criticism. Third, interpretation, which is interpreting the data obtained so that it becomes a fact. The last stage of historiography is to write history. The results of this study show that two father figures with different backgrounds, the first is the Jamarun family. Second, Intan Mara's family. The Jamarun family succeeded in educating their children, in contrast to the Intan Mara family where Intan Mara's children were disappointed and eventually disobedient. Intan Mara's children are not stupid or left behind, it's just that they do not get direction and support in continuing their education.